PENERAPAN KOLABORASI TUTOR SEBAYA DENGAN METODE JIGSAW DALAM MENINGKATKAN KEAKTIFAN BELAJAR SEJARAH INDONESIA SISWA KELAS XII IS 1 SMA NEGERI 1 MOYO UTARA - Mahendrayati, Bhinneka (CV Sintesia, 2024)
Students' enthusiasm for face-to-face learning during the COVID-19 pandemic has decreased, especially the active learning of Indonesian history material for class XII IS 1 SMAN 1 Moyo Utara. This makes the teacher's thinking, because the teacher's job is to condition students to learn actively. So that his potential (affective, cognitive and psychomotor) can develop to the fullest. For this reason, a teacher must master learning strategies and be able to choose media and learning methods in achieving learning objectives. The collaboration of peer tutors with the jigsaw method can increase students' active learning. In this study, the Kemmis and Taggart models were chosen, which consisted of planning, implementing, observing and reflecting. The implementation is in two cycles with a sample of class XII IS 1 of SMAN 1 Moyo Utara for the academic year 2021/2022, totaling 27 students. Based on the results of observations during the teaching and learning process and direct interviews as well as filling out questionnaires with qualitative and quantitative descriptive analysis techniques, the average results in the first cycle are 63.3% and the second cycle is 79.80%. 63.30%. Thus there is an increase of 16.5% from cycle I to cycle II, classified as active. Thus, it can be concluded that the collaboration of peer tutors with the jigsaw method can increase the active learning of students of SMAN 1 Moyo Utara regarding Indonesian History.